Humor in Families and Stress Reduction: The Mediating Role of Positive Affect - Rahman, Farhana; Mokoena, Thandiwe (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the relationship between humor and stress in families, with positive affect as a mediating variable. Methods and Materials: The study employed a descriptive correlational design with 409 participants selected from families in South Africa, based on the Morgan and Krejcie sample size table. Data were collected through standardized questionnaires measuring humor, stress, and positive affect. Pearson correlation analysis was conducted using SPSS-27 to explore bivariate associations among variables. Structural Equation Modeling (SEM) was performed in AMOS-21 to test the hypothesized mediation model. Model fit was evaluated using multiple indices, including χ², df, χ²/df, GFI, AGFI, CFI, TLI, and RMSEA. Findings: The results revealed significant correlations between the study variables. Humor was positively correlated with positive affect (r = 0.53, p < .001) and negatively correlated with stress (r = −0.41, p = .001). Stress showed a significant negative correlation with positive affect (r = −0.47, p < .001). The structural model demonstrated acceptable fit (χ²(61) = 124.36, χ²/df = 2.04, GFI = 0.93, AGFI = 0.90, CFI = 0.96, TLI = 0.95, RMSEA = 0.049). Path analysis confirmed that humor had a direct positive effect on positive affect (β = 0.39, p < .001) and a negative effect on stress (β = −0.34, p = .001). Stress negatively influenced positive affect (β = −0.28, p < .001). Positive affect mediated the relationship between humor and stress, with a significant indirect effect (β = 0.09, p = .002). Conclusion: The findings highlight the protective role of humor in family contexts, showing that it reduces stress both directly and through the mediating role of positive affect. Integrating humor into family-based interventions may enhance resilience and emotional well-being.